Understanding the impact of a clinical care pathway for major head and neck cancer resection on postdischarge healthcare utilization. (18th September 2015) - Dautremont, Jonathan F.; Rudmik, Lucas R.; Nakoneshny, Steven C.; Chandarana, Shamir P.; Matthews, T. Wayne; Schrag, Christiaan; Fick, Gordon H.; Dort, Joseph C.
Abstract: Background: The purposes of this study were to explore the association of a postoperative clinical care pathway for patients undergoing major head and neck surgery with microvascular reconstruction on postdischarge health care utilization and cost and to compares a nonpathway group ( n  = 60) to a prospective, pathway‐managed group ( n  = 54). Our primary purpose was to understand whether pathway‐managed patients used postdischarge health care resources differently than patients managed without a care pathway. Methods: Health care utilization data (counts and costs) were collected for the 3 months after discharge. Differences in utilization were compared using Poisson regression. The null hypothesis was that there were no differences in utilization between the pathway and nonpathway groups. Results: Pathway patients had fewer postdischarge encounters in 2 of 4 sectors. Readmission costs were significantly less in the pathway group only. Conclusion: A postoperative inpatient clinical care pathway in patients with head and neck cancer is associated with decreased health care utilization and inpatient costs in the 3 months after discharge. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1216–E1220, 2016